Voice over IP security a comprehensive survey of vulnerabilities and academic research - Keromytis, Angelos D. (SpringerBriefs in Computer Science, 2011)
Voice over IP (VoIP) and Internet Multimedia Subsystem technologies (IMS) are rapidly being adopted by consumers, enterprises, governments and militaries. These technologies offer higher flexibility and more features than traditional telephony (PSTN) infrastructures, as well as the potential for lower cost through equipment consolidation and, for the consumer market, new business models. However, VoIP systems also represent a higher complexity in terms of architecture, protocols and implementation, with a corresponding increase in the potential for misuse. In this book, the authors examine the current state of affairs on VoIP security through a survey of 221 known/disclosed security vulnerabilities in bug-tracking databases. We complement this with a comprehensive survey of the state of the art in VoIP security research that covers 245 papers. Juxtaposing our findings, we identify current areas of risk and deficiencies in research focus. This book should serve as a starting point for understanding the threats and risks in a rapidly evolving set of technologies that are seeing increasing deployment and use. An additional goal is to gain a better understanding of the security landscape with respect to VoIP toward directing future research in this and other similar emerging technologies.